Sports Nutrition Sciences: an essential overview - Negro, M.; Rucci, S.; Buonocore, et al., D. (Progress in Nutrition, 2013)
The topic of sports nutrition has received considerable attention over thepast few decades, and it is likely to get even more attention, given that nutritionplays such an important and sometimes crucial role in an athlete’s performance.Indeed, nutrition influences nearly every process in the body involvedin energy production and recovery from exercise. To understand andapply the principles of sport nutrition, some basic understanding of nutrition,exercise physiology and sport science are necessary.The nutritional approachfor training and competition is one of the most important concernsof sport nutrition science. Exercise produces several molecular, biochemicaland physiological responses and the aim of a well designed diet is to guaranteea correct intake of energy, carbohydrates, proteins, fats, vitamins, mineralsand water in order to support basic nutrition requirements as well aspre-, during and post-exercise specific nutrition phases. A very interestingsubject of sport nutrition is the use of supplements and their effects on humanperformance and health.The number of supplements introduced to themarket is huge, however, only few products are apparently effective andscientifically proven by a solid core of reference. For many other supplementsnormally used by athletes, the data are anecdotic or based on only afew studies and thus their use cannot be universally recommended. A keyitem in sport nutrition is the manipulation of body mass and body composition.Reducing fat mass is desirable in many sports with weight categoriesand increasing muscle mass can be an advantage in sports that requirestrength and power. Finally, nutritional requirements can be different forwomen, young and elderly athletes. These categories have different age andsex-related physiological needs and specific nutrition strategies must beplanned to guarantee adequate exercise adaptation and maintain overallhealth. Scienza della Nutrizione dello Sport: una panoramica essenziale La nutrizione applicata allo sport ha ricevuto una considerevole attenzionenegli ultimi 10 anni; un’attenzione destinata ad aumentare in quantol’alimentazione gioca un ruolo chiave, talvolta determinante nelle prestazionidi un atleta. In effetti, l’alimentazione incide su quasi tutti i processi fisiologicicoinvolti nella produzione di energia e nel recupero muscolare. Per comprendere e applicare i principi della nutrizione sportiva, sono necessarie conoscenzedi base della nutrizione, fisiologia dell’esercizio e scienza dellosport. L’approccio nutrizionale per l’allenamento e la competizione è uno deitarget più importanti di cui si occupa la scienza della nutrizione dello sport.L’esercizio fisico produce diverse risposte molecolari, biochimiche e fisiologichee l’obiettivo di una dieta ben programmata è quello di garantire un correttoapporto di energia, carboidrati, proteine, grassi, vitamine,minerali e acqua,al fine di soddisfare le specifiche richieste nutrizionali delle fasi pre-,durante e post-attività fisica. Un argomento molto interessante trattato dallanutrizione dello sport è l’uso di supplementi e la comprensione dei loro effettisulle prestazioni fisiche e sulla salute umana. Il numero di supplementiintrodotti sul mercato è enorme, tuttavia, solo pochi prodotti sono statiscientificamente testati mostrando una certa efficacia. Per molti altri prodotti,normalmente utilizzati dagli atleti, i dati sono aneddotici o ricavati da pochistudi, e quindi il loro uso non può essere raccomandato. La nutrizionesportiva si occupa, inoltre, di studiare le variazioni di massa e composizionecorporea negli atleti. La riduzione della massa grassa è auspicabile in moltisport che contemplano categorie di peso, mentre un aumento di massa muscolarepuò essere un vantaggio negli sport che richiedono forza e potenza.Infine, le richieste nutrizionali possono essere diverse per donne, atleti giovanied anziani. Queste categorie hanno diverse esigenze fisiologiche legate asesso ed età per cui specifiche strategie nutrizionali devono essere pianificateper garantire sia i meccanismi di adattamento all’esercizio fisico, sia il mantenimentodello stato di salute.